Lobbyists in Spain: professional and academic profiles - Castillo-Esparcia, Antonio; Moreno-Cabanillas, Andrea; Almansa-Martínez, Ana María (MDPI, 2023)
Public relations are fundamental in organisations to establish an adequate relationship between the company and its public, and in the field of relations with public authorities, lobbying has become a very important activity. Two types of action can be distinguished: direct lobbying and grassroots lobbying. The aim of this research is to determine the professional and academic profiles of Spanish lobbyists to determine which type of activity is most common. To achieve this, the professional profiles of 370 Spanish lobbyists were analysed on LinkedIn, and a questionnaire was sent to them to find out about their experience, academic background, and typical activities. The results indicate that Spanish lobbyists are organised around companies and consultancies specialising in political communication and communication advice. The need to formalise lobbying activity, explain its tasks, recognise the exercise of influence, and establish an official register is highlighted. Regarding academic training, new Spanish lobbyists have studied Communication with postgraduate degrees in Political Science and Sociology rather than legal studies, as previously thought. There is also a growing presence of women in this field. In addition, it was determined that 88% of Spanish lobbyists focus on direct lobbying, and only 12% focus on grassroots lobbying.
Keywords: Reuniones; Relaciones públicas; Comunicación empresarial; Lobbyists; Public affairs; Communication; Academic profile; Professional profile